Intestinal epithelial Gasdermin C is induced by IL-4R/STAT6 signaling but is dispensable for gut immune homeostasis - Reyes Gámez-Belmonte; Yara Wagner; Mousumi Mahapatro; Ru Wang; Lena Erkert; Miguel González-Acera; Roodline Cineus; Saskia Hainbuch; Jay V. Patankar; David Voehringer; Ahmed N. Hegazy; Markus F. Neurath; et al. (Scientific Reports)
Abstract Gasdermin C is one of the least studied members of the gasdermin family of proteins, known for their critical involvement in pyroptosis and host defense. Furthermore, evidence for the role of Gasdermin C in the intestine is scarce and partly controversial. Here, we tested the functional role of Gasdermin C in intestinal homeostasis, inflammation and tumorigenesis. : We studied Gasdermin C in response to cytokines in intestinal organoids. We evaluated epithelial differentiation, cell death and immune infiltration under steady state conditions in a new mouse line deficient in Gasdermin C. The role of Gasdermin C was analyzed in acute colitis, infection and colitis-associated cancer. Gasdemin C is highly expressed in the intestinal epithelium and strongly induced by the type 2 cytokines IL-4 and IL-13 in a STAT6-dependent manner. Gasdermin C-deficient mice show no changes in tissue architecture and epithelial homeostasis. Epithelial organoids deficient in Gasdermin C develop normally and show no alterations in proliferation or cell death. No changes were found in models of acute colitis, type 2 intestinal infection and colitis-associated cancer. Gasdermin C genes are upregulated by type 2 immunity, yet appear dispensable for the development of intestinal inflammation, infection and colitis-associated cancer.